The Role of Amanah and Financial Solvency in Improving Financial Performance: Literature Review (Architecture Image Studies, 2025)
This study explores the integration of Amanah (trustworthiness) within the concept of financial solvency to enhance corporate financial performance. Drawing upon Capital Structure and Trade-Off Theories, it develops a new paradigm called Amanah Financial Solvency (AFS), a fusion of financial prudence and Islamic ethical stewardship. Through a comprehensive literature review from Scopus, WoS, ScienceDirect, and Emerald databases, this study reveals that Amanah transforms solvency from a mere financial ratio into a moral construct grounded in accountability, transparency, and integrity. Theoretically, AFS extends traditional solvency frameworks by embedding moral consciousness into financial decision-making. Empirically, it bridges inconsistencies in solvency performance relationships by introducing Amanah as a moderating factor. The study concludes that sustainable financial performance arises not only from rational optimization but also from the ethical equilibrium between profitability, responsibility, and divinity.